2017
DOI: 10.21474/ijar01/4058
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Maxillary Jaw Bone Assessment Using Cone Beam Computed Tomography of a Diabetic Versus a Nondiabetic Sample of Egyptian Population.

Abstract: Background and purpose:Evaluation of maxillary bone is very essential for the diagnosis, treatment planning, and management of maxillofacial procedures. This study aimed to evaluate the maxillary jaw bone quality and quantity in a sample of Egyptian patients with diabetes mellitus (DM) compared to another nondiabetic sample using Cone Beam Computed Tomography (CBCT) and also to correlate between the maxillary jaw bone quality and quantity and other factors as glycated haemoglobin (HbA1c) values, disease durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In the present study, no subject in any group showed mean height less than the prescribed height <11 mm. Many studies have evaluated height parameter at various implant sites, some have measured it at the midline,[ 6 21 ] at edentulous sites,[ 6 32 33 34 ] some have measure it near the premolar region with inclusion of safe distance from anterior loop,[ 6 35 ] some have conducted prospective studies where implants were placed in prospectively[ 36 ] Studies which evaluated the width parameter are scarce and involve methods formulated by the researchers for standardization;[ 21 35 ] however, it must be realized that height and width are interdependent quantities but often height adjustments are done to accommodate for the necessary adequate width. The present study is unique in the sense that all the prescribed prospective implant site[ 26 ] have been measured for the height parameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, no subject in any group showed mean height less than the prescribed height <11 mm. Many studies have evaluated height parameter at various implant sites, some have measured it at the midline,[ 6 21 ] at edentulous sites,[ 6 32 33 34 ] some have measure it near the premolar region with inclusion of safe distance from anterior loop,[ 6 35 ] some have conducted prospective studies where implants were placed in prospectively[ 36 ] Studies which evaluated the width parameter are scarce and involve methods formulated by the researchers for standardization;[ 21 35 ] however, it must be realized that height and width are interdependent quantities but often height adjustments are done to accommodate for the necessary adequate width. The present study is unique in the sense that all the prescribed prospective implant site[ 26 ] have been measured for the height parameter.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ] Kenawy et al ., in 2017, compared bone resorption and bone density between diabetic and nondiabetic patients and found no significant difference between bone quantity, there was decreased bone density in diabetic patients. [ 33 ] Taylor et al ., in 1998, tested and proved the hypothesis that noninsulin-dependent diabetes mellitus patients have a higher progression of residual ridge resorption. [ 42 ] the present study supports these findings as the ORI was found to be lower in diabetic patients as compared to nondiabetics.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT technique was used to assess the mandibular bone density related to the edentulous bounded saddle. Before performing any measurements, a precise panoramic curve was accurately drawn on a selected axial cut at approximately the mid-tooth level of the mandibular teeth (14). The inferior alveolar nerve canal was accurately traced until the mental foramen using the panoramic image.…”
Section: Methodsmentioning
confidence: 99%